Gold standard motion analysis system for evaluating jumping performance in rhythmic gymnastics - Coppola, S.; Costa, C.; Vastola, R. (Journal of Human Sport & Exercise, 2023)
The aim of this study is to investigate the effectiveness, not yet described in the literature, of the gold standard system for motion analysis, to analyse the kinematic and dynamic aspects of the split leap in rhythmic gymnastics performed with and without the ribbon. The sample consists of six top level gymnasts aged between 13 and 16 (mean 15.1 ± 0.94). The acquisitions were carried out with the integrated multifactorial optoelectronic system BTS Bioengineering. Fifteen passive markers, six BTS Smart-DX cameras, two cameras for video support and seven BTS-6000 force platforms were used. After the acquisition of the gymnasts' anthropometric measurements, a standardized and specific neuromuscular activation was carried out. The software SMART tracker and SMART analyser were used to process and analyse the dynamics and kinematics data. A questionnaire was administered to the gymnasts to collect information regarding training. The results showed no major differences in force impulse, jump amplitude, elevation and flight time between the trials performed with and without ribbon. The experiment conducted demonstrates the effectiveness of using the integrated multifactor optoelectronic system to carry out the kinematic and dynamic analysis of a highly complex sports technique.